Performing the high bitrate visible light communications in the foggy weather to anticipate the interference on vehicle communications - Brian Pamukti; Achmad Yanatun; Kris Sujatmoko; Hurianti Vidyaningtyas (JURNAL INFOTEL, 2022)
We propose transmission media with visible light to communicate between vehicles. We evaluate the research under four scenarios using the modulation of On-Off Keying Non-Return to Zero (OOK-NRZ) and bitrate up to 1 Gbps. These scenarios are (i) ideal conditions, (ii) interference from other vehicle lights, (iii) foggy conditions, and (iv) interference from vehicles and fog conditions. Based on the extensive simulation, the results obtained are that interference and fog conditions can affect and reduce the value of the signal to interference and noise ratio (SNR) and increase the value of the error rate (BER). The results obtained are that interference and fog conditions can affect and reduce the value of the signal to interference and noise ratio (SNR) and increase the value of the error rate (BER). The SNR value in the first scenario is 23.6 dB and the second scenario is 11.1 dB, where this value is still sufficient. The SNR in scenario three is 16.1 dB, and the lowest in the fourth scenario is -7.78326 dB, indicating that the noise is extensive compared to signal power. In addition, we also obtain an optimal distance of communication between vehicles for each scenario sequentially 14.5 m, 13 m, 11.5 m, and 9 m.